CONSCIÊNCIA POLÍTICA E PREDISPOSIÇÃO A PARTICIPAÇÃO DOS TRABALHADORES DAS BIBLIOTECAS DA UFES EM AÇÕES COLETIVAS DO SINTUFES - Coelho, Francisco Felipe (2020)
This paper analyzes how the political conscience and the predisposition to the participation of UFES library servants in the collective actions of SINTUFES during the 2014 to 2019 management are configured. It adopts as a theoretical framework the Analyt